MELANKOLIS DALAM SENI GRAFIS - ADHATUL AKBAR, Drs. Ariusmedi, M. Sn., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2019)
Aiming at visualizing melancholy as something that gives social instability in one’s life and environment, through surrealism graphic art.In the creation of a work of art, it is necessary to make various preparations, including making observations, information seeking, appreciation, contemplation, extracting references, and literature relating to the initial idea, as well as indirectly deepening the material around the environment according to these problems.Through this graphic art the author develops in the form of work of art, some works of art that have been presented exclusively namely: behind the scene, sadness, sacrifice, comfort in solitude, comfort in silence, pessimism, pressed, listener, thinkers, and romance. This is the main point of troubling things in life from melancholy.Keywords: Melancholy in Graphic Art.